ANALISIS KINERJA KEUANGAN PADA KOPERASI BKPT - Hendi Rohendi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2015)
Abstract : This research aimed to analyze the finance performance of cooperation BKPT in 2014, The object of the research was to analyze the financial statement position and income statement. The method used in this research was quantitative descriptive with documentation data collection techniques, which obtained from its financial statement then its value is determined through several ratios and compared with the regulation of the undang-undang koperasi No:14/per/M.KUKM/XII/2009. the result for liquidity, showed that BKPT cooperative was liquid, the efficient level was efficient, but the component of profitability was not maximized.